Rickettsial infection in ticks (Acari: Ixodidae) of wild animals in midwestern Brazil - Witter, Rute; Martins, Thiago F.; Campos, Artur K.; Melo, Andréia L.T.; Corrêa, Sandra H.R.; Morgado, Thaís O.; Wolf, Rafael W.; May-Júnior, Joares A.; Sinkoc, Afonso L.; Strüssmann, Christine; Aguiar, Daniel M.; Rossi, Rogério V.; et al. (Ticks and Tick-borne Diseases, 2016)
Ticks collected in the last two decades from free-living and captive wild animals from 28 municipalities of the Brazilian state of Mato Grosso were identified and tested using molecular methods for the presence of rickettsial agents. A total of 4467 ticks (229 larvae, 1676 nymphs, 1565 males, 997 females) representing 27 ixodid species were collected from 235 species of amphibians, reptiles, birds, and mammals from three different ecoregions (Pantanal, Cerrado, and Amazonia). The species Amblyomma parkeri, Amblyomma romitii, Amblyomma varium and Ixodes luciae are reported for the first time in the state of Mato Grosso. Amongst 538 ticks tested by molecular methods for rickettsial infection, we detected ‘Candidatus Rickettsia amblyommii’ infecting Amblyomma cajennense sensu stricto and Amblyomma coelebs, Rickettsia sp. strain Atlantic rainforest infecting Amblyomma ovale, Rickettsia sp. strain NOD infecting Amblyomma nodosum, and ‘Candidatus Rickettsia andeanae’ infecting Amblyomma sculptum. Our results represent an impressive expansion of knowledge on tick fauna and rickettsiae and are essential for understanding the ecology of ticks and tick-borne diseases in the Neotropical region, particularly in midwestern Brazil.
Keywords: Tick-borne diseases; Rickettsia; Amazonia; Cerrado; Pantanal